(untitled) (Eurasian Research Bulletin, 2026)
The twentieth century occupies a special place in the history of Japanese literature. This period was characterized by significant political, social, and cultural transformations that influenced literary development. The modernization process, Western cultural influence, World War II, and postwar reconstruction shaped new literary trends and artistic expressions. Japanese writers combined traditional aesthetic values with modern literary techniques, creating works of international significance. Authors such as Natsume Sōseki, Ryūnosuke Akutagawa, Yasunari Kawabata, Yukio Mishima, and Kenzaburō Ōe contributed greatly to the evolution of Japanese literature and its recognition worldwide. This article examines the major stages of twentieth-century Japanese literary development, highlighting the influence of modernism, war experiences, and postmodern tendencies on literary creativity